2011
DOI: 10.1016/j.ajpath.2011.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Chromatin Remodeling Factor, RSF-1/HBXAP, Correlates with Aggressive Oral Squamous Cell Carcinoma

Abstract: RSF-1, also known as hepatitis B X-antigen associated protein (HBXAP), is a subunit of an ISWI chromatin remodeling complex, remodeling and spacing factor (RSF). Recent studies have provided new evidence that chromatin remodeling participates in the pathogenesis of neoplastic diseases by altering cell cycle regulation and gene expression. In this report, we studied the biological roles of RSF-1 in oral squamous cell carcinoma (OSCC), a highly invasive neoplastic disease. Based on IHC and quantitative real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 40 publications
5
30
0
Order By: Relevance
“…The results, suggesting that high RSF1 expression indicates a poor prognosis of RCC, are consistent with data in ovarian, prostate and hepatocellular cancer (17,18,21). The results may be explained by previous studies demonstrating that RSF1 promotes tumor cell proliferation and invasion (10,13,14,16). All of these results together suggest that RSF1 is an important oncogene in RCC.…”
Section: Event-free Survivalsupporting
confidence: 81%
See 2 more Smart Citations
“…The results, suggesting that high RSF1 expression indicates a poor prognosis of RCC, are consistent with data in ovarian, prostate and hepatocellular cancer (17,18,21). The results may be explained by previous studies demonstrating that RSF1 promotes tumor cell proliferation and invasion (10,13,14,16). All of these results together suggest that RSF1 is an important oncogene in RCC.…”
Section: Event-free Survivalsupporting
confidence: 81%
“…Accumulating evidence indicates that chromatin remodeling is associated with the regulation of malignant cell transformation and tumor progression Amplification of genes at the 11q13.5 locus is common in solid tumors, including ovarian, head and neck, and breast carcinomas (12,13,15,(23)(24)(25)(26). The genes of the region include RSF1, EMSY, BRCA2 interacting transcriptional repressor, P21 (RAC1) activated kinase 1 (PAK1), RAD9 checkpoint clamp component A, and cyclin D1 have been proposed as candidate tumor driver genes (12,13,15,(23)(24)(25)(26). Numerous studies have demonstrated that the amplification of RSF1 is not only significantly correlated with tumor cell proliferation, migration, invasion and apoptosis abilities, but also with poor prognosis of patients with ovarian, lung, hepatocellular and prostate cancer (14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been shown that Rsf-1 is overexpressed in cancer cells rather than in normal cells. [25][26][27][28][29] To confirm clearly if the recruitment of Rsf-1 at DSBs is not specific in cancer cells, we immunostained the endogenous Rsf-1 with γH2AX at 10 min after micro-irradiation in normal human RPE1 and U2OS cancer cells, and found that Rsf-1 is indeed co-localized with γH2AX at the micro-irradiated sites in both cell lines (Fig. 1C).…”
Section: Rsf-1 Is Recruited At Dsb(s)mentioning
confidence: 99%
“…24 As a subunit of RSF complex, Rsf-1 has been studied in clinical research, and its overexpression has been found in many types of cancer patients. [25][26][27][28][29] Recent studies about Rsf-1 showed that Rsf-1 overexpression induces DNA damage response through ATM-Chk2-p53-p21 pathway and inhibits cell cycle progression followed by apoptosis and chromosome instability. [30][31][32] Even if Rsf-1 has been implicated in response to DNA damage, the biological function of Rsf-1 still remains unclear.…”
Section: Reportmentioning
confidence: 99%